2019
DOI: 10.14716/ijtech.v10i6.3595
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Yield and Physicochemical Properties of Pectin Isolated from Citrus Maxima

Abstract: Citrus maxima white pith was utilized for the isolation of pectin under acidified condition using L-(+)-tartaric acid, at extraction pH in the range of 1.0 and 2.0. The extraction yield and physicochemical properties (ash content, equivalent weight, methoxy content, anhydrouronic acid, degree of esterification) of the isolated pectin was investigated. The highest yield (70.2%) obtained in this extraction was at pH 1.0, 60°C, 120 minutes. The optimized condition of the isolated pectin in this study was based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The degree of esterification (DE) is the principal property for pectin application in the food industry, as it controls the gel‐forming effect of pectin (Daud et al., 2019). The DE of pectin obtained in the present study was found as 67.91 ± 0.33 (Table 5), which was found in the range: 63.29 ± 0.84–75 ± 0.53% of DE was reported from orange peels pectin extracted using citric acid (Sayah et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of esterification (DE) is the principal property for pectin application in the food industry, as it controls the gel‐forming effect of pectin (Daud et al., 2019). The DE of pectin obtained in the present study was found as 67.91 ± 0.33 (Table 5), which was found in the range: 63.29 ± 0.84–75 ± 0.53% of DE was reported from orange peels pectin extracted using citric acid (Sayah et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Where: 176 g/mol – molecular weight of AUA; z – the volume of NaOH in equivalent weight, y – the volume of NaOH in methoxyl content, and W – sample weight, g . Degree of esterification: It was determined through MeO and AUA content (Daud et al., 2019). This was obtained as: …”
Section: Materials and Methodologymentioning
confidence: 99%
“…These chemicals were used as received without any further purifications. Pectin used in this study was extracted from pomelo (Citrus maxima) pith in our laboratory, and the detailed extraction procedure has been previously reported [39]. Double distilled water was used throughout experiments.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…3000 ve 3780 cm -1 arasındaki karakteristik bandlar polisakkarit moleküllerindeki hidroksil grubunun O-H gerilmesini göstermektedir. Polisakkarit moleküllerindeki karboksilik asit -COOH ve hidroksil gruplarının hidrojen bağı yapmasından kaynaklanabilen bu absorpsiyon bandı pektin FTIR spektrumlarında gözlenmektedir [65]. Yaklaşık olarak 2980-2800 cm -1 'deki band galakturonik asitin alkil gruplarının (CH, CH2, CH3) C-H gerilmesini göstermektedir [65], [66].…”
Section: Ftir (Fourier Transform Infrared) Analiziunclassified
“…Polisakkarit moleküllerindeki karboksilik asit -COOH ve hidroksil gruplarının hidrojen bağı yapmasından kaynaklanabilen bu absorpsiyon bandı pektin FTIR spektrumlarında gözlenmektedir [65]. Yaklaşık olarak 2980-2800 cm -1 'deki band galakturonik asitin alkil gruplarının (CH, CH2, CH3) C-H gerilmesini göstermektedir [65], [66]. Tüm numuneler için ortak olan ve pektin fonksiyonel grubuna işaret eden yaklaşık 1730 cm -1 ve 1650-1510 cm -1 civarındaki soğurma bandları; sırasıyla esterlenmiş karbonil gruplarının C=O ve serbest karbonil gruplarının C=O gerilme titreşimine karşılık gelir [67].…”
Section: Ftir (Fourier Transform Infrared) Analiziunclassified